Pengaruh Pemberian Rebusan Daun Kelor Terhadap Kelancaran Produksi Asi Pada Ibu Nifas - Kamelia Sinaga; Asnita Sinaga; Imran Saputra Surbakti; Ninsah Mandala Putri; Rumondang (PublisihingId, 2022)
Latar Belakang: World Health Organization (WHO) merekomendasikan dua hal penting yang harus dilakukan yaitu, memberikan air susu ibu kepada bayi segera dalam waktu 30 menit setelah bayi lahir, dan memberikan hanya ASI saja atau pemberian ASI secara eksklusif. Rendahnya cakupan ASI di Indonesia menyebabkan akibat yang tidak baik bagi kesehatan bayi. Salah satu upaya yang dilakukan untuk meningkatkan suplai ASI adalah dengan mengkonsumsi rebusan daun kelor yang dipercaya mengandung senyawa fitosterol yang berfungsi meningkatkan dan memperlancar produksi ASI. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian rebusan daun kelor terhadap kelancaran produksi ASI di Desa Desa Beringin kecamatan beringin Tahun 2021. Jenis penelitian ini adalah Quasy Eksperiment dengan rancangan penelitian One Group Pretest-Posttest, dengan menggunakan teknik sampel jenuh dengan jumlah sampel 20 orang. Hasil penelitian menunjukkan bahwa rata-rata kelancaran produksi ASI sebelum diberikan rebusan daun kelor adalah 4,00 dengan standar deviasi 1,622, sedangkan rata-rata kelancaran produksi ASI setelah diberikan rebusan daun kelor adalah 6,15 dengan standar deviasi 1,137. Dari analisis data dengan menggunakan uji Wilcoxon didapatkan P value (0,000) < a (0,05), maka dapat disimpulkan bahwa H0 ditolak dan Ha diterima. Diharapkan pada tenaga kesehatan untuk agar menggunakan rebusan daun kelor sebagai alternative untuk meningkatkan produksi ASI pada ibu nifas Background: World Health Organization(WHO) recommends two important things to do namely, giving breast milk to the baby immediately within 30 minutes after the baby is born, and giving only breast milk or exclusive breastfeeding. The low coverage of breast milk in Indonesia contributes a bad effect on the health of infants. One of the efforts made to increase the supply of breast milk is by consuming boiled moringa leaves which are believed to contain phytosterol compounds that function to increase and facilitate milk production. This study aims to determine the effect of Moringa leaf decoction on the smooth production of breast milk in Beringin districts beringin in 2021. This type of research is Quasy Experiment with One Group Pretest-Posttest research design, using saturated sample technique with a sample of 20 people. The results showed that the average smoothness of ASI production before given Moringa leaf decoction was 4.00 with a standard deviation of 1.622, while the average smoothness of ASI production after given Moringa leaf decoction was 6.15 with a standard deviation of 1.137. From the data analysis using the Wilcoxon test, it was obtained that P value (0,000) <a (0.05), it can be concluded that H0 was rejected and Ha was accepted. It is expected that health workers should use boiled Moringa leaves as an alternative to increase milk production in postpartum mothers. From the data analysis using the Wilcoxon test, it was obtained that P value (0,000) <a (0.05), it can be concluded that H0 was rejected and Ha was accepted. It is expected that health workers should use boiled Moringa leaves as an alternative to increase milk production in postpartum mothers. From the data analysis using the Wilcoxon test, it was obtained that P value (0,000) <a (0.05), it can be concluded that H0 was rejected and Ha was accepted. It is expected that health workers should use boiled Moringa leaves as an alternative to increase milk production in postpartum mothers